Time-Dependent Impairment of Fear Conditioning and Associated Brain Regions After Pilocarpine-Induced Status Epilepticus - Qiu, Xiangmiao; Kinoshita, Masako; Peng, Anjiao; Li, Wanling; Lai, Wanlin; Wang, Jing; Zhang, Lin; Chen, Lei (Frontiers in Behavioral Neuroscience, 2020)
Our study aims to demonstrate time-dependent declarative memory changes and its associated brain regions after status epilepticus (SE) using structural imaging techniques and machine learning methods. Pilocarpine was administrated to establish SE model. At different four time points after SE (One, two, three, and four months respectively), rats were subjected to structural imaging acquisition as well as contextual fear conditioning for measurement of brain structural changes and declarative memory. Voxel-based morphometry (VBM) analysis were performed. Those significantly different regions were selected as features for training support vector machines (SVM). A linear kernel was chosen for regression of declarative memory. Leave-one-out cross validation was applied to ensure generalization. Our results showed that the pilocarpine groups displayed most severely impaired declarative memory at two months after SE and improved afterwards, but fail to recover to the normal condition at 4 months after SE. The pilocarpine groups showed lower gray matter volumes and larger CSF volumes. After controlling for the total brain volumes, ANOVA analysis demonstrated gray matter volume changes in CA1 subfield of hippocampus, primary somatosensory cortex, entorhinal cortex, etc. Combination of VBM and SVM identifies somatosensory cortex and entorhinal cortex as correlated brain regions for declarative memory dysfunctions after SE. Our study indicates that compensational mechanisms might be triggered to help with the recovery of memory functions after SE. Structural changes of somatosensory cortex and entorhinal cortex might involve in memory impairment after SE.